2019
DOI: 10.1016/j.apsusc.2019.01.015
|View full text |Cite
|
Sign up to set email alerts
|

The Oscillatory Adsorption of Organosilane Films on Aluminium Oxide: Film Morphology using Auger Electron Spectromicroscopy

Abstract: The morphology of Propyltrimethoxysilane films during the oscillatory growth mechanism is shown using Auger Electron Spectromicroscopy. While the link between oligomerisation of silane molecules on the substrate and the oscillatory growth mechanism has been proposed previously, here for the first time we show the presence of silane film islands through Auger Electron Spectromicroscopy elemental mapping of the substrate. Monitoring the morphology of the film at key peaks and throughout along the oscillatory cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…In order to remove and replace the existing oxide layer, creating a reproducible surface for silane condensation, aluminium substrates were abraded with 1200 grade wet-dry sandpaper, rinsed with Milli-Q water and ultrasonicated in a pH3 acetic acid solution at room temperature for one hour. Previous studies have shown this method to result in a reproducible oxide layer [16]. 1% v / v silane solutions were prepared in a 1:1 H 2 O:EtOH solvent altered to pH 3 with glacial acetic acid and stirred until the silane solution was considered hydrolysed through observing complete dissolution of silane in the aqueous solvent [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to remove and replace the existing oxide layer, creating a reproducible surface for silane condensation, aluminium substrates were abraded with 1200 grade wet-dry sandpaper, rinsed with Milli-Q water and ultrasonicated in a pH3 acetic acid solution at room temperature for one hour. Previous studies have shown this method to result in a reproducible oxide layer [16]. 1% v / v silane solutions were prepared in a 1:1 H 2 O:EtOH solvent altered to pH 3 with glacial acetic acid and stirred until the silane solution was considered hydrolysed through observing complete dissolution of silane in the aqueous solvent [8].…”
Section: Methodsmentioning
confidence: 99%
“…A curing procedure is often performed on silane films in order to force the dynamic equilibrium condensation reaction to completion; with curing shown to create more siloxane bonds, decrease film thickness and increase film density when compared to uncured films [15]. The density of PTMS on aluminium oxide has been mapped and depth profiled with results indicating the presence of two different film morphologies on the surface of un-rinsed films in the form dense, highly oligomerised islands surrounded by a monolayer-like film [16]. In theory, forced removal of water from the film via curing results in a film containing only covalently bound silane species ( θ 2 of the 2-component model).…”
Section: Introductionmentioning
confidence: 99%
“…A promising environmentally friendly pre-treatment is found in organofunctional silanes. The bifunctional molecule with a central silicon atom, interacts with the oxidized metal surface creating a film of interlinked siloxane molecules, usually in the thickness range from ten to hundreds of nanometres [13]. This three-dimensional network is resistant to hydrolysis, offering corrosion protection [14].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is significant, as it has been suggested through the use of AES elemental mapping that PTMS films contain both thin, monolayer like films in conjunction with large, oligomerized islands. 15 However, despite AES having outstanding spatial resolution, the morphology of these films cannot be measured on a molecular scale. The stabilization of the SFG CH 3(s) /CH 2(s) shown in Figure 7 appears to correspond with the thin, monolayer observed using AES 15 but provides molecular level resolution.…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of surface characterization techniques such as X-ray photoelectron spectroscopy (XPS), AES, and NEXAFS presents an issue in that they require the sample to be placed in an ultrahigh vacuum environment for analysis and thus these measurements cannot be conducted in solution, nor in situ. The ability to measure the conformation of molecules during the film self-assembly process and directly compare this to the time-dependent oscillatory adsorption reported previously [7][8][9][10][11]15,16 will provide much insight into the mechanisms involved in silane film self-assembly. For this, alternative techniques such as sum frequency generation spectroscopy (SFG) which can be conducted on samples both in situ and ex situ must be considered.…”
Section: Introductionmentioning
confidence: 94%